Association between flood-prone geographies and incomplete ANC in India: Implications for equitable maternal care access - Rakesh Chandra; Jeetendra Kumar Patel; Sonal Srivastava; Saradiya Mukherjee; Aditya Singh (Social Sciences and Humanities Open)
This study examines the association between floods and incomplete antenatal care (ANC) visits in India to assess the impact of floods on ANC utilization, particulary among vulnerable groups. Data from the National Family Health Survey (2019–20) and Vulnerability Atlas of India (2019) were used and merged to create individual-level data. Binary logistic regression was employed to analyze the odds of incomplete ANC visits, adjusting for relevant variables. Interaction terms were incorporated to investigate the moderating effects of wealth (poor and non-poor) and social groups [Scheduled Caste (SC)/Scheduled Tribes (ST) and non-SC/ST]. Flood-prone districts showed a 50 % higher likelihood of incomplete ANC visits. When examining the interaction effects, wealth was found to be insignificant in flood-prone regions. Women from SC/ST households in flood-prone areas were two times more likely to have incomplete ANC visits compared to the rest. Floods have a significant association with poor ANC utilization in India. The heightened odds of incomplete ANC visits in flood-prone districts underscore the need for targeted interventions. Moreover, the amplified disparity between SC/ST and non-SC/ST women in flood-prone areas emphasizes the urgency of addressing inequities. We suggest policymakers and healthcare providers to develop inclusive strategies that ensure equitable access to maternal healthcare amid the increasing risks posed by floods and other extreme events associated with climate change, with a strong emphasis on effectively prioritizing vulnerable populations.